Bilateral Ureteral-Iliac Artery Fistula in a Patient with Chronic Indwelling Ureteral Stents: A Case Report and Review - Arash Rafiei; Timothy A. Weber; Michael Kongnyuy; Raul Ordorica (Case Reports in Urology)
Ureteral-arterial fistula (UAF) is an exceedingly rare but life-threatening condition warranting emergent intervention. Prompt recognition and management of UAF in suspect patients presenting with gross hematuria are required for a successful outcome. We report a rare subset of UAF involving the bilateral common iliac arteries. The patient underwent successful endovascular stent-grafting to correct the arterial defect and delayed open repair of the ureteral strictures. Timely management has benefited from the collaboration of the involved medical teams, which included emergency medicine, urology, and interventional radiology.